The relationship between GDP and happiness in EU countries - Tao, Jing (2022)
Composite indicators make rankings efficient because they provide a multi-dimensional and comprehensive picture of a phenomenon that cannot be depicted by only one indicator. The study reviews existing measures of well-being and composite indicators and a new happiness indicator is constructed to rank EU countries according to OECD (2008) as a guide. Discussion relationship between happiness and GDP in the EU, after removing the extreme values it is shown that happiness is positively correlated with GDP level. However, no statistically significant trend is identified with GDP per capita above 50,000 $ countries. Finally, further research it may be necessary to construct happiness indicators more comprehensively to rank countries' happiness more accurately. It is needed to deeply explore the relationship with happiness when GDP per capita is grouped in the future study.